Numerical and experimental analysis of a natural ventilation windcatcher with passive heat recovery for mild-cold climates. (February 2019) - Calautit, John; O'Connor, Dominic; Shahzad, Sally; Calautit, Katrina; Hughes, Ben
Abstract: In this work, a novel design incorporating a passive heat recovery device into a windcatcher was proposed and investigated using numerical and experimental analysis. The proposed system incorporates a rotary thermal heat recovery in the windcatcher channel. Computational Fluid Dynamics (CFD) was used to investigate the effect of the heat recovery device on the performance of the windcatcher, highlighting the capabilities of the system to deliver the required fresh air rates. The windcatcher model was incorporated to a 5m x 5m x 3m test room model representing a small classroom. The study employed the CFD code Fluent18 with the k-epsilon model to conduct the simulations. The numerical model provided detailed analysis of the airflow and temperature distribution inside the test room. A 1:10 scale prototype of the system was created and tested experimentally in a closed-loop subsonic wind tunnel to validate the CFD investigations. Despite the blockage of the rotary t heat recovery wheel, ventilation rates were able to provide adequate ventilation. In addition to sufficient ventilation, the heat in the exhaust airstreams was captured and transferred to the incoming airstream, raising the temperature between 1-4K depending on the indoor/outdoor conditions, this passive recovery has the potential to reduce demand on space heating systems. According to WBCSD, a recovery of 3 K from the exhaust stream to the inlet stream could generate energy savings up to 20% in heating costs. This shows that the concept has significant potential to be developed further, whereby the heat transfer properties of the system can be investigated and tested on a larger scale.